2017
DOI: 10.1002/glia.23269
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 regulates astrocytic and vascular development in the retina

Abstract: Sox2 is a transcriptional regulator that is highly expressed in retinal astrocytes, yet its function in these cells has not previously been examined. To understand its role, we conditionally deleted Sox2 from the population of astrocytes and examined the consequences on retinal development. We found that Sox2 deletion does not alter the migration of astrocytes, but it impairs their maturation, evidenced by the delayed upregulation of glial fibrillary acidic protein (GFAP) across the retina. The centro-peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Astrocyte maturation is regulated by classic regulators, such as SOX2, which is a highly conserved transcriptional factor in all stages of central nervous system development. 42 Dentin matrix protein 1-proteoglycan (DMP1-PG) 43 and astrocytic contact 44 are also required for astrocyte maturation.…”
Section: Yap Governs Astrocytic Maturation Via the Secretion Of Lifmentioning
confidence: 99%
“…Astrocyte maturation is regulated by classic regulators, such as SOX2, which is a highly conserved transcriptional factor in all stages of central nervous system development. 42 Dentin matrix protein 1-proteoglycan (DMP1-PG) 43 and astrocytic contact 44 are also required for astrocyte maturation.…”
Section: Yap Governs Astrocytic Maturation Via the Secretion Of Lifmentioning
confidence: 99%
“…However, if microglia mediate clearance but not death, ablation would be expected to increase the number of corpses without a similar increase in the number of differentiated astrocytes. To distinguish between these possibilities we stained microglia-ablated retinas for GFAP, a late marker of retinal astrocyte differentiation that also reveals cellular morphology [28,30,56]. Nearly all (>98.8%) Pax2 + or Sox9 + astrocytes co-expressed GFAP by P10, regardless of whether microglia had been ablated (Control: n=2,642 astrocytes; DTR: n=4,145 astrocytes; N=3 animals per condition).…”
Section: Ablation Of Microglia Increases Astrocyte Numbermentioning
confidence: 99%
“…Previous study using Cag-CreER T2 :Sox2 fl/fl mice has reported that SOX2 deletion does not affect astrocyte development in the spinal cord (11). In contrast, SOX2 is recently reported to regulate astrocyte maturation in the retina of hGFAP-Cre:Sox2 fl/fl mice (17). However, hGFAP-Cre mediates gene disruption in embryonic multi-potential NSCs, NSC-derived glial/neuronal cells, and retinal Muller glia as indicated by reporter gene expression (18).…”
Section: Introductionmentioning
confidence: 97%
“…Astroglial-specific SOX2 deletion paradigms are necessary to study the role of SOX2 in astrocyte maturation in vivo. Furthermore, much of our current knowledge of SOX2 in astrocyte development is largely based on GFAP immunostaining (11,17), which displays intrinsic limitations for astrocyte visualization despite its importance in assessing astrocyte maturation. The direct delineation of the role of SOX2 in postnatal astrocyte development and animal behavior is still very limited, and how SOX2 regulates astrocyte maturation is largely unknown.…”
Section: Introductionmentioning
confidence: 99%